PENGEMBANGAN MODEL KOMUNIKASI PARIWISATA BERBASIS EKOWISATA DI KAMPUNG ADAT YOKIWA, DISTRIK SENTANI TIMUR, KABUPATEN JAYAPURA - Robinhot Sagala; Alienra Nanda Kadunr (Jurusan Ilmu Komunikasi Universitas Andalas, 2022)
Traditional Yokiwa village has a lot of potential as a tourist destination, but it hasn't been managed effectively. The aim of this study is to learn more about the traditional tourism communication model used in Yokiwa Village. This study employs a descriptive methodology with a qualitative approach. Data was obtained through interviews with village heads, communities, and local government officials. The results show that a multi-step communication model can be used to improve tourism communication in the Yokiwa traditional village. The development of a communication model based on ecotourism is the development of ecotourism by involving stakeholders. By focusing on aspects of nature protection, aspects of socio-cultural economic empowerment of the local community.